Tool kit for public private partnerships in urban primary health centers in India. (Asian Development Bank, 2020)
It can be used by all states, regardless of where they are in the development and realization of their strategy, policies, and processes with respect to PPPs in UPHCs. For states that already have such a program, this may help to streamline and improve policies and processes. It also contains guidelines and suggestions that are useful for states that are open to or considering the implementation of similar programs.